16 Mouthguard usage during sport: participants' perspective. (20th December 2017) - Karaganeva, R; Taylor, R; Burden, A; Tomlinson, D; Pinner, S; Winwood, K
Abstract : Orofacial traumas account for a third from all injuries sustained during contact sports. Wearing a mouthguard (MG) could reduce the risk of such injuries. Yet, there is an underlying belief amongst many players that the device could cause impedances with comfort, breathing and speech. This might be due to the type of MG or athletes knowledge of which one is best. For example, custom-made MGs were found to provide superior protection and fit compared to 'boil-and-bite' or stock MGs. The aim of the present study was to examine the current attitudes and awareness of MGs in the UK via online questionnaire. An online survey was distributed to 308 participants via email and social media, which consisted of 18 questions, addressing the usage of mouth protection in different levels of sport (e.g. national/international), rate of dental injuries and common issues previously raised within the literature. The results showed that 23% of the 308 respondents competed at national level, 15% at international and 10% were part of a club. The majority were rugby union players (57%) and the rest participated in sports such as ice hockey (17%), martial arts (5%) and other team sports. It was found that 40% currently wore a customised MG, however many of them had experienced problems with discomfort and breathing. Almost half of the respondents highlighted that they had stopped wearing a MG due to the device being uncomfortable. These factors are raised quite considerably throughout the literature and within this study; it is therefore a recommendation that these issues need to be addressed. More education about why customised MGs should be worn is required to improve usage and compliance as well as improving manufacturing techniques to reduce the highlighted issues.